hancement of Learning Outcome Quality SMK Business Skills and Management in Bandung City - Santoso, Budi; Imaniati, Nani; Adman, Adman (International Journal of Engineering and Technology, 2018)
The problem studied in this research is not yet optimal competence qualityÂ of Vocational High School (SMK) Bandung city. This is evident from the problem of the low graduation rate and the unemployment rate in Indonesia is a phenomenon of the quality of graduate competence that has not been optimal. The purpose of this research is to get the concept of Vocational High School (SMK) education in Bandung City in improving the quality of competence so that it can produce skilled workers from qualified vocational high school (SMK) graduates and in line with the needs of employment. Technique of collecting data using questionnaire with ordinal scale. While the method used is Explanatory Survey Method. Respondents size 150 teachers, taken randomly from 30 Vocational School Skills Program Business and Management in Bandung. Data processing techniques using path analysis. Based on the data analysis, it can be concluded that (1) the leadership of the principal has a strong, positive, and significant influence on teacher teaching performance and teacher work motivation; (2) Principal leadership, teacher teaching performancse and teacher work motivation, have a positive and significant impact on the learning process; (3) Headmaster leadership, teacher teaching performance and teacher work motivation, and learning process, have positive and significant impact on the quality of graduate competence. Recommendations proposed that the intervention of the foundation of the principal's policies should be reduced. The principal should strive to foster motivation and teaching standards that have been adapted to the 2013 curriculum, making it easier for teachers to convey the content of learning in teaching and learning activities in schools.Â